Contemporary Problems of Librarian’s Profession - Синкявичюс, Клеменсас (Knygotyra, 1973)
During this century libraries that formerly represented archives of literature or museums availabille for a few have become the centres of education and sources of information, offices for public use of books. At the same time the demand for library specialists has been constantly growing. The first schools of library science appeared by the end of the last century. At present librarians are trained in most countries of the world. The number of students at these schools is constantly growing, too.Due to a rapid development of science and technology there exists a discrepency between the urge towards training specialists not only in library science but also as experts in some other fields of science and the possibility of putting it into practice. It is suggested that the above problem could be solved through making up the staff of librarians both of specialists in library science and experts in other fields of science, at the same time giving them special knowledge required for their collaboration.For optimum use of the books in stock, to meet the demands of the public, libraries should be joined up in several types (systems). In training librarians the stock of general knowledge contributing to the collaboration among the libraries of different types is of prime importance. Specialized knowledge (according to the given library type) favouring a better collaboration among specialists in other fields of science is of less importance.In preparing a new curriculum at the Chair of Library Science and Scientific Information of the Vilnius V. Kapsukas State University, the principal of the professional structure of library workers, the general and special shares in the professional training of a librarian were taken into account.